2005
DOI: 10.4049/jimmunol.174.3.1222
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Production of IL-10 by Dendritic Cells Deficient in CIITA

Abstract: Dendritic cells (DC) are professional APCs that play a critical role in regulating immunity. In DC, maturation-induced changes in MHC class II expression and Ag presentation require transcriptional regulation by CIITA. To study the role of CIITA in DC, we evaluated key cell functions in DC from CIITA-deficient (CIITA−/−) mice. The ability to take up Ag, measured by fluid phase endocytosis, was comparable between CIITA−/− and control DC. Although CIITA−/− DC lack MHC class II, they maintained normal expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 47 publications
1
39
1
Order By: Relevance
“…This suggests that CIITA is highly dedicated to the regulation of MHC-II expression. Nevertheless, a series of reports have implicated CIITA in the regulation of a wide variety of other genes functioning within and outside the immune system [8][9][10][11][12][13][14]20]. These reports suggested that CIITA might play a pleiotropic role in various biological processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that CIITA is highly dedicated to the regulation of MHC-II expression. Nevertheless, a series of reports have implicated CIITA in the regulation of a wide variety of other genes functioning within and outside the immune system [8][9][10][11][12][13][14]20]. These reports suggested that CIITA might play a pleiotropic role in various biological processes.…”
Section: Discussionmentioning
confidence: 99%
“…The genes encoding IL-4 and Fas ligand (FasL) were proposed to be repressed by CIITA in mouse T cells [8,9]. Those encoding cathepsin E and IL-10 were suggested to be repressed by CIITA in mouse B cells and/or DC [10,11]. The genes encoding collagen type Ia2, thymidine kinase and cyclin D1 were proposed to be repressed by CIITA in IFN-c-induced cells [12].…”
Section: Molecular Immunologymentioning
confidence: 99%
“…The list of transcription factors that activate IL10 production is increasing; however, only a handful of transcription factors are known to repress its expression (23). Transcription factors ETS1 and T-bet repress IL10 expression in Th1 cells, BCL-6 inhibits IL10 production in Th2 cells, MHC class II transactivator (CIITA) negatively regulates IL10 expression in mouse dendritic cells, and BCL-3 represses IL10 production in macrophages (23,(45)(46)(47)(48). However, the quest for master regulators with a direct binding site on the IL10 promoter still remains.…”
Section: Discussionmentioning
confidence: 99%
“…T2 and Priess, provided by Dr. J. Blum (Indiana University, Indianapolis, IN), were grown in IMDM with the same supplements. Mouse splenic B cells were prepared as described previously (34).…”
Section: Cellsmentioning
confidence: 99%